Mapping of Iran’s Scientific Publication and Position in the Field of Library and Information Science in the Website of “Web of Science” During 1994-2009 - Zahra Behzadi; Abdulrasul Jowkar (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2011)
Purpose: This research was conducted with the aim of evaluating Iran’s scientific populations in the field of library and information science during 1994-2009. Methodology: Citation analysis was used. The population under study included all documents (paper, report, critical paper, etc.) presented by Iranian researchers in the field of library and information science which have indexed in “Web of Science” website during 1994-2009. In order to search for these documents in this database, initially all journals related to LIS which are indexed in the JCR unit of the “Web of Science” website were identified (61 journals). Then, Iran’s scientific publications in these 61 LIS journals were investigated. Besides, annual growth of Iran’s publications was calculated based on exponential regression. Findings: According to R2 value related to annual growth of scientific publications, Iran’s rate of scientific growth during the mentioned 16 years has been significant (P<0.05). The results indicated that Iran has gained a 33% growth rate during the years under study. Investigation of the document types showed that the Iran’s 96 records were presented in four different formats and only in English, and the highest populated format was “paper”. Furthermore, evaluation of the journals’ impact factor revealed that Iranian researchers have published their papers more in journals with low impact factors. The highest impact factor belonged to the “Journal of Informatics”, in which only two papers from Iran were published. Also, the clusters in the historiography mapping based on LCS and GCS are depicted, as well as the top researchers in this field. The results showed that the geographical location, speaking with the same language, and working on the same topic are effective on the number of citations at global and local levels. Originality: It is an effort to study the scientific publications of Iran in the field of LIS, so as to provide an insight for policy-makers and research managers.